Perceived impact on coastal reclamation activities in a fishing community in Johor, Malaysia - Jumain, Nora Azura (2018)
Fisheries community is the community that highly depends on the fisheries sector and they usually live near the coastal area. This is because the coastal area has natural ecosystem that is vital for the productivity of fisheries such as seagrass beds and mangrove. However, reclamation activities are conducted at the coastal area for the sake of development and urbanization due to the increasing population. Consequently, the reclamation activities had degraded the habitat of the fishes and cause the decreasing in the productivity of fishes. Thus, the specific objectives of this study were to examine the differences between fishing operations, fish catch and income of fishermen before and after reclamation; to determine the perception of fishermen towards reclamation activities; to explore the most influential factors that influence the fish catch of fishermen and to determine the relationship between the number of crew, fish catch and income of fishermen. A total of 79 fishermen that catch fish near the Merambong Shoal were selected as respondents whereby a structured questionnaire was constructed to conduct the study. The Paired Sample t-test result showed that there was a difference in mean between fishing operations, fish catch and income before and after reclamation. The mean of fish catch before reclamation activity started was 23.6 kg whereas the mean of fish catch decreased to 12.9 kg after the reclamation activity started. This showed that the fish catch of fishermen had decreased as an impact of reclamation activities. The mean ranking analysis results showed that fishermen had a negative perception towards the reclamation activities that was conducted at the coastal area. The multiple regression analysis revealed that the number of trips, duration of fishermen to catch fish, distance of fishing ground from the coast, number of crew and government incentives were the factors that affected the fish catch. Meanwhile, number of crew became the most influential factor that affected the quantity of fish catch. These independent variables have significant relationships with the quantity of fish catch which directly impacted the income and at the same time affected the livelihoods. Pearson correlation analysis was conducted to determine the strength of relationship between the fish catch, income, and number of crew. The results showed that these three variables have a positive significant relationship with each other. There was a weak relationship between fish catch and income while the relationship between number of crew and income showed a medium relationship. This indicated that the quantity of fish catch and number of crew in a vessel affected the income of the fishermen. With regard to the findings, the role of government in improving the fish catch of fishermen was highly recommended. It is recommended that the government should increase the monetary incentives and subsidies to improve the fishing operations of the fishermen.